Contribution à l’étude de la reproduction du poisson Luciobarbuscallensis (Cyprinidae) de barrage OuldjetMellegue à Tébessa - Cheddad Sorour; Triaa Hadia (My University, 2022)
Our work aims to contribute to the study of reproduction and parasitism by gill monogeneans of an autochthonous fish of the Cyprinidae family widely distributed in Algeria Luciobarbuscallensisduring a sampling period of four months (from February to May 2022) at the OuldjetMellegue dam reservoir (Tébessa). The sex ratio of the sampled population is in favor of females throughout the period sampling and in the small and large sizes, on the other hand it is in favor of the males in the medium sizes. The follow-up of the monthly evolution of the two parameters (RGS, RHS) of L. callensis showed that the maximum values are recorded in May. On the other hand, the condition index K records its lowest values in May. The parasitic study allowed us to collect 53 ectoparasiticmonogene. The observation of their morpho-anatomical criteria reveals the presence of two species of monogeneansDactylogyrusheteromorphusand Dactylogyrus sp. ---------------------------------------------------------------------------------------------------------------------------------------------------- يهدفعملناإلىالمساهمةفيدراسةالتكاثروالتطفلعنطريقأحاديةالعائلالخياشميهللأسماكالمحلية منعائلةCyprinidaeالمتواجدةعلىنطاقواسعفيالجزائرLuciobarbuscallensisوذلكلمدة أربعةأشهر )تراوحتبينفبرايرإلىمايو 2022 ( علىمستوىسدولجةملاق )تبسة( . النسبةبينالجنسينفيالعينةالمأخوذةلصالحالإناثطوالفترةهذهالدراسةوكذلكعندالأحجامالصغيرة والكبيرة،ومنناحيةأخرىفإنقيمهذاالمؤشرلصالحالذكورفيالأحجامالمتوسطة. أظهرتمراقبةالتطورالشهريللمعاملين ) RGS ،RHS ( منLuciobarbuscallensisأنهتم تسجيلالقيمالقصوىفيشهرمايو. منناحيةأخرى،سجلمؤشرالحالةK أدنىقيملهفيشهرمايو. سمحتلناالدراسةالطفيليةبجمع 53 طفيليًاخارجيًاأحاديًالعائل. ملاحظةالخصائصالمورفولوجية أسفرتعنوجودنوعينمنالطفيلياتأحاديةالعائلDactylogyrusheteromorphus وDactylogyrussp. ------------------------------------------------------------------------------------------------------------------------------------------------------ Notre travail a pour but de contribuer à l'étude de la reproduction et le parasitisme par les monogènes branchiaux d'un poisson autochtone de la famille Cyprinidae largement répandue en Algérie Luciobarbuscallensispendant une période d'échantillonnage de quatre mois (de février à mai 2022) au niveau de la retenue de barrage OuldjetMellegue (Tébessa). La sex-ratio de la population échantillonnée est en faveur des femelles durant toute la période d’échantillonnage et dans les petites et les grandes tailles, en revanche il est en faveur des mâles dans les moyennes tailles. Le suivie de l’évolution mensuelle des deux paramètres (RGS, RHS) de L. callensisa montrés que les valeurs maximales sont enregistré en moi de mai. En revanche, l’indice de condition K enregistre ses valeurs les plus basses en mois de mai. L’étude parasitaire nous a permis de récolter 53 monogènes ectoparasites. L’observation de leurs critères morpho-anatomique révèle la présence de deux espèces de monogènesDactylogyrusheteromorphuset Dactylogyrussp.